Disseminated Burkitt lymphoma presenting as massive gastrointestinal bleed. Issue 3 (2nd July 2020) - Harne, Prateek Suresh; Macklin, Jared; Muniraj, Thiruvengadam
Abstract: Burkitt lymphoma is a rare, highly aggressive non-Hodgkin lymphoma with increasing incidence. Here we present a 26-year-old man with a history of a recent root canal who presented with 2 days of black, tarry stools, persistent tooth pain, and 2 weeks of fatigue, night sweats, and a 20-pound weight loss. He developed massive hematemesis while hospitalized and an esophagogastroduodenoscopy revealed innumerable, doughnut-shaped masses with central umbilication throughout the stomach, which were also the source of bleeding. Targeted biopsies revealed Burkitt lymphoma. After prompt chemotherapy treatment, repeat endoscopy showed complete resolution of all gastric masses, and the mucosa appeared normal.